Frequency stability and under frequency load shedding of the Southern Sulawesi power system with integration of wind power plants. Issue 1 (March 2020) - Arief, A; Nappu, M B; Sultan, A
Abstract: The Government of Indonesia is encouraging investments in renewable energy based power plants in Indonesia, including wind power plants (WPPs). Two large WPPs in the Southern Sulawesi interconnected power system are Sidrap WPPs and Jeneponto WPPs. Both Sidrap WPP and Jeneponto WPP are the largest WPPs in Indonesia and they account for significant contribution for the Southern Sulawesi power generation mix. Considering the intermittency characteristics of WPPs and system's failure probability, therefore it is essential to assess the system's stability after their integration. This work evaluates the frequency stability of the Southern Sulawesi interconnected power system with the integration of both Sidrap WPPs and Jeneponto WPPs.